Novel Drug Combinations in Lung Cancer: New Potential Synergies Between 5-FU and Repurposed Drugs - Eduarda Ribeiro; Nuno Vale (Applied Sciences)
The therapeutic potential of combining 5-FU with repurposed drugs such as Sildenafil, Tezosentan, Levosimendan, and Resveratrol was investigated in lung cancer treatment using the A549 cell line. This study aimed to enhance 5-FU efficacy while mitigating side effects and overcoming drug resistance. The cytotoxic effects of 5-FU were assessed via MTT assay, with an IC50 value of 5.03 µM for A549 cells. Subsequent experiments evaluated the impact of combining 5-FU with the aforementioned drugs on cell viability, clonogenic potential, and morphology. The results demonstrated that while Sildenafil and Tezosentan modestly improved 5-FU efficacy, Levosimendan reduced cell viability by 40% (p < 0.01) and Resveratrol by over 50% (p < 0.001), with clonogenicity reduced by up to 60% (p < 0.001). These findings suggest that combining 5-FU with Levosimendan or Resveratrol offers promising approaches for lung cancer therapy, potentially reducing the need for higher doses of 5-FU and minimizing associated toxicity. Future studies are warranted to elucidate the mechanisms underlying these interactions and assess their clinical relevance.